Rapid microbial evaluation of acute exacerbations of bronchiectasis using FilmArray Pneumonia plus Panel in a real-world setting - Charles Wong; Chun Wai Tong; Hei Shun Cheng; Pui Hing Chiu; Flora Pui Ling Miu; Yiu Wing Lam; Loretta Yin Chun Yam (Therapeutic Advances in Respiratory Disease)
Background: Acute exacerbations of bronchiectasis (AEB) are frequently caused by bacterial and/or viral infections. Rapid multiplex polymerase chain reaction (PCR) panels in respiratory specimens have significantly advanced microbial evaluation in patients with pneumonia. However, their clinical utility in patients with AEB remains unknown. Objectives: To investigate the microbial characteristics of AEB using FilmArray Pneumonia plus Panel (FAPP) and explore its clinical impact in a real-world setting. Design: A cross-sectional study. Methods: Spontaneous sputum samples of patients hospitalized for AEB were tested using FAPP in addition to standard-of-care testing. Microbial characteristics of AEB and the clinical impact of FAPP were evaluated. Results: Among 83 patients, FAPP detected ⩾1 bacterial pathogen(s) in 68 samples (81.9%), identifying 101 bacteria, with high abundance (10 6 to ⩾10 7  copies/ml) observed in 48 patients (57.8%). The most commonly detected bacteria were Pseudomonas aeruginosa ( Pa ) (37/83, 44.6%), Staphylococcus aureus (21/83, 25.3%), and Haemophilus influenzae (13/83, 15.7%). Respiratory viruses were identified in 21 patients (25.3), with Influenza A and Respiratory syncytial virus being the most common. Culture detected bacteria in significantly fewer samples ( n  = 25 [30.1%], p  < 0.001). FAPP demonstrated 100% positive percent agreement and negative predictive value for all cultured bacteria, except for Corynebacterium striatum ( n  = 2), which was not included in the panel. FAPP shortened the time to bacterial results (mean: 10.8 h vs 70.8 h by culture, p  < 0.001), and led to antimicrobial changes in 25 patients (30.1%) before the culture results were available. In multivariate analysis, chronic Pa infection (odds ratio (OR) 14.71), underweight status (OR 5.84), and cystic bronchiectasis (OR 5.26) were independent predictors of Pa detection by FAPP. Conclusion: The sputum multiplex PCR panel (FAPP) enables rapid identification of bacterial and viral pathogens in AEB, supporting early antimicrobial decision-making. Our findings highlight the potential utility of sputum multiplex PCR panels in improving the management of bronchiectasis exacerbations.